A Progressivism in Character Education and Social Issues in the Biography Novel of Buya Hamka: A Sociopragmatic Perspective": Progresivisme Pendidikan Karakter Kesalihan Sosial pada Novel Biografi Buya Hamka Prespektif Sosiopragmatik - Gusti Yanti, Prima; Sukardi, Edi; APRIYADI, HENDRA (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2024)
This research aims to analyze the content of progressivism in character education and social virtue embedded in the biography novel of Buya Hamka, utilizing a sociopragmatic study approach. The prophetic sociopragmatic study approach is employed to investigate the social and pragmatic context of Buya Hamka's perspective on character education and social virtue in the novel. The study also identifies how these values can be implemented in the context of character education in Al Islam and Kemuhammadiyahan. The research methodology adopts a qualitative approach with content analysis techniques to explore various aspects of progressivism in character education and social virtue within the novel. Data are analyzed by considering the historical, social, and religious contexts that shape Buya Hamka's views on character education and social virtue, using a socioprakmatic perspective.